Ultraviolet-B Radiation Effects on Growth and Physiology of Four Rice Cultivars - Dai, Qiujie; Coronel, Victoria P.; Vergara, Benito S.; Barnes, Paul W.; Quintos, Arlene T. (Wiley, 1992)
Enhanced ultraviolet‐B (UV‐B, 280–320 nm) radiation, such as could be caused by stratospheric O, depletion, has been demonstrated to profoundly affect plants. This study was conducted to determine the effects of UV‐B on four high‐yielding, lowland rice (Oryza sativa L.) cultivars (IR30, IR45, IR64, and IR74), and to evaluate morphological and physiological parameters for identifying sensitive and less‐sensitive genotypes in future screenings. Ultraviolet‐B radiation was supplied by UV‐B–emitting fluorescent lamps in the phytotron. Plant height, leaf area, dry weight, net assimilation rate (NAR), and relative growth rate (RGR) were significantly influenced by 4‐wk UV‐B treatment in some cultivars. Based on the relative change in total biomass production between UV‐B‐irradiated and control plants, cultivar IR74 was the most sensitive and cultivar IR64 the least sensitive. Biomass production, however, did not proportionally decrease with plant height under UV‐B treatment. Changes in plant height and leaf area induced by UV‐B can alter the rice plant canopy structure. Differential varietal response was found in shoot dry weight, leaf area, specific leaf weight (SLW), NAR, and RGR. These parameters can be used as selection criteria for rice cultivars less sensitive to UV‐B. Most physiological and biochemical parameters evaluated, including root‐oxidizing activity, soluble protein, nucleic acid, ion leakage, stomatal aperture, and flavonoid and chlorophyll contents, were affected by 2 wk of UV‐B treatment and gave differential cultivar responses. The distinct responses and relative ease in measurement of stomatal opening and ion leakage make these parameters suitable indices in selecting rice cultivars less sensitive to UV‐B after 2 wk of UV‐B treatment.